Epicardial adipose tissue thickness in patients with urolithiasis - Burak Altun; Eyup Burak Sancak; Berkan Resorlu; Hakan Tasolar; Alpaslan Akbas; Gurhan Adam; Mustafa Resorlu; Mehzat Altun (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Aim: We aimed to assess the relationship between urinary stone disease which is accepted as a component of metabolic syndrome and epicardial adipose tissue (EAT) thickness. Methods: The study included 45 patients and 39 healthy controls. EAT thickness was measured by echocardiography in all subjects. Results: EAT thickness was higher (5.77±0.88 vs. 3.83±0.72mm, p<0.001) in patients than in control subjects. EAT thickness was correlated with age, triglyceride levels, low density lipoprotein cholesterol levels and family history. Regression analysis showed that family history, triglyceride levels and age were independent predictors of EAT thickness in kidney stone patients. Conclusion: We suggest that urolithiasis should be considered as a component of metabolic syndrome and EAT thickness may be useful to detect early atherosclerosis in urolithiasis.